2009
DOI: 10.1111/j.1600-0404.1992.tb04046.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of erythrocyte aggregability and plasma fibrinogen concentration on CBF with aging

Abstract: The influence of the rheological properties of the blood on cerebral perfusion is still unresolved. Data on normal subjects are lacking and difficulties arise regarding the effect of blood viscosity owing to its close relationship with hematocrit. For these reasons we have studied the relationship between two rheological hematocrit‐independent parameters and CBF in normal subjects of various ages. 36 normal volunteers, aged 20–74, free from risk factors, have been studied. CBF was measured by the Xenon inhalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Insufficient cerebral perfusion may result in neuronal damage and subsequent decline in cognitive function [ 20 ]. An early study of Cavestri et al [ 6 ] found a significant negative correlation between CBF and fibrinogen levels in subjects over age 45. Peter et al [ 12 ] showed strong relationships between significantly better cognitive performance and faster reaction times and lower levels of plasma viscosity although they thought the plasma fibrinogen concentration had no significant relationship with cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient cerebral perfusion may result in neuronal damage and subsequent decline in cognitive function [ 20 ]. An early study of Cavestri et al [ 6 ] found a significant negative correlation between CBF and fibrinogen levels in subjects over age 45. Peter et al [ 12 ] showed strong relationships between significantly better cognitive performance and faster reaction times and lower levels of plasma viscosity although they thought the plasma fibrinogen concentration had no significant relationship with cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The normal aging process in the healthy brain is linked to a decrease in physiological function possibly due to the constant increase in neuroinflammation [ 55 ]. Clinical studies have reported that Fgn is an abundant protein in human blood plasma at concentrations ranging from 1.5–4 mg/mL with a normal half-life of 3–5 days, and the plasma concentration of Fgn increased progressively with age in healthy subjects [ 56 60 ]. Although the neuroinflammatory protein, Fgn, has shown an age-related increase in blood, which has been documented in major epidemiological studies [ 56 60 ], little is known about the pathological mechanism(s) of this increase in Fgn levels with age.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that Fgn is an abundant protein in human blood plasma at concentrations ranging from 1.5–4 mg/mL with a normal half-life of 3–5 days, and the plasma concentration of Fgn increased progressively with age in healthy subjects [ 56 60 ]. Although the neuroinflammatory protein, Fgn, has shown an age-related increase in blood, which has been documented in major epidemiological studies [ 56 60 ], little is known about the pathological mechanism(s) of this increase in Fgn levels with age. Fgn infiltration and BBB dysfunction are characteristic features of several neurological diseases [ 61 64 ] and Fgn has been detected in the frontal cortex and hippocampal regions of Alzheimer’s disease brain tissue [ 65 ].…”
Section: Discussionmentioning
confidence: 99%